(untitled) (Jurnal Manajemen dan Organisasi, 2017)
Good corporate governance defines the correlation among corporate’s elements which can determine the performance of the corporation. By implementing GCG within the corporates, it is expected to increase corporate performance improvement in both financial and non-financial sector. The purposes of this research is to analyze how the implementation of GCG and the performance of PT Asuransi Jasa Indonesia and how the GCG’s influence towards corporate performance. The analytical method used in this research is multiple linear regression analysis. The analysis result shows that the GCG implementation was not significantly effect PT Asuransi Jasa Indonesia performance. Accountability has significantly effect to PT Asuransi Jasa Indonesia performance. The coefficient determination (R2) was 0,187 (18,7%) showed that GCG implementation was still has small contribution to PT Asuransi Jasa Indonesia performance.